2004
DOI: 10.1637/7080
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pathobiology of Low and High Pathogenicity H7N3 Chilean Avian Influenza Viruses in Chickens

Abstract: Chickens were intranasally inoculated with Chilean H7N3 avian influenza (AI) viruses of low pathogenicity (LP) (H7N3/LP), high pathogenicity (HP) (H7N3/HP), and a laboratory derivative (02-AI-15-#9) (H7N3/14D) from the LPAI virus to determine pathobiologic effects. All chickens inoculated with H7N3/HP AI virus became infected and abruptly died 2 or 3 days postinoculation, but a few showed moderate depression before death. The H7N3/HP AI virus produced focal hemorrhages of the comb, petechial hemorrhage at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 20 publications
5
37
0
Order By: Relevance
“…Similar viral replication and lesion distribution have been seen in other intravenous experiments using low-pathogenicity AIVs in chickens (33,35,36). By contrast, highly pathogenic AIVs on intranasal or intravenous inoculation typically produce systemic virus infection, including viremia, with virus replication and necrobiotic lesions in multiple visceral organs, brain, and skin (8,10,18,25,40).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Similar viral replication and lesion distribution have been seen in other intravenous experiments using low-pathogenicity AIVs in chickens (33,35,36). By contrast, highly pathogenic AIVs on intranasal or intravenous inoculation typically produce systemic virus infection, including viremia, with virus replication and necrobiotic lesions in multiple visceral organs, brain, and skin (8,10,18,25,40).…”
Section: Discussionsupporting
confidence: 58%
“…In the current study, the low-pathogenic parent virus did not change in virulence following passage in the 14-day-old ECE passage model system, and all the resulting derivatives had biological characteristics of low-pathogenicity AIVs, including lack of plaque formation in the chicken embryo fibroblasts in the absence of added trypsin, absence of high mortality in intravenous pathotyping tests, and virus demonstration and lesions limited to epithelial cells. However, the presence of viral antigen in some cardiac myocytes of derivative 2-inoculated chickens is a pattern seen with highly pathogenic AIVs (8,10,18). This could represent an early stage in the transition from low-to high-pathogenicity AIV.…”
Section: Discussionmentioning
confidence: 95%
“…Remarkable findings were observed that differed from the natural disease. Firstly, fibrinous peritonitis was a usual macroscopic lesion described during the H7N1 HPAIV natural outbreak Mutinelli et al, 2003), but was not observed in the present experimental infection or in other HPAIV experimental infections (Swayne, 1997(Swayne, , 2007Perkins & Swayne, 2001;Jones & Swayne, 2004;Swayne & Beck, 2005). Fibrinous peritonitis is a very common lesion in commercial birds, associated with secondary bacterial infections (Barnes et al, 2008) and its description in a natural outbreak can reflect a simultaneous viral脕 bacterial infection (Zanella, 2003;Swayne & Halvorson, 2008).…”
Section: Discussionmentioning
confidence: 73%
“…Myocardial necrosis or myocarditis with IHC-positive cardiomyocytes is commonly observed in all the species mentioned above (Perkins & Swayne, 2001;Antarasena et al, 2006;Isoda et al, 2006;Bertran et al, 2011Bertran et al, , 2013, sometimes together with myocyte necrosis and positive myocytes in the skeletal muscle (Perkins & Swayne, 2001;Bertran et al, 2011Bertran et al, , 2013. The HPAIVs, especially the Eurasian H5N1 HPAIVs, are generally defined as neurotropic (Perkins & Swayne, 2001;Jones & Swayne, 2004;Swayne & PantinJackwood, 2008) and are thought to reach the central nervous system via the haematogenous route . Frequent lesions in the brain are lymphocytic meningoencephalitis with neuronal necrosis, neuronophagia, and focal gliosis (Figure 2c) (Perkins & Swayne, 2001;Isoda et al, 2006;Bertran et al, 2011Bertran et al, , 2013.…”
Section: Pathobiology Of Hpaivs In Minor Gallinaceous Speciesmentioning
confidence: 99%